2012
DOI: 10.1038/tp.2012.68
|View full text |Cite
|
Sign up to set email alerts
|

NAAG peptidase inhibitors block cognitive deficit induced by MK-801 and motor activation induced by d-amphetamine in animal models of schizophrenia

Abstract: The most widely validated animal models of the positive, negative and cognitive symptoms of schizophrenia involve administration of d-amphetamine or the open channel NMDA receptor blockers, dizocilpine (MK-801), phencyclidine (PCP) and ketamine. The drug ZJ43 potently inhibits glutamate carboxypeptidase II (GCPII), an enzyme that inactivates the peptide transmitter N-acetylaspartylglutamate (NAAG) and reduces positive and negative behaviors induced by PCP in several of these models. NAAG is an agonist at the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 68 publications
4
46
1
Order By: Relevance
“…To further demonstrate that pharmacological inhibition of STEP was sufficient to ameliorate the behavioral effects arising from NMDAR antagonism, we used another NMDAR blocker, MK-801, which has been widely validated as a pharmacological model of SZ and induces motor and cognitive deficits in mice 39-41 . In agreement with previous reports 42, 43 , we found MK-801 treatment induced hyperactivity (SI Figure 11a-c) and memory deficits in the Y-maze and novel object recognition tasks (SI Figure 11d, e); these deficits were significantly reversed by pretreatment with TC-2153 (SI Figure 11a-e).…”
Section: Resultsmentioning
confidence: 99%
“…To further demonstrate that pharmacological inhibition of STEP was sufficient to ameliorate the behavioral effects arising from NMDAR antagonism, we used another NMDAR blocker, MK-801, which has been widely validated as a pharmacological model of SZ and induces motor and cognitive deficits in mice 39-41 . In agreement with previous reports 42, 43 , we found MK-801 treatment induced hyperactivity (SI Figure 11a-c) and memory deficits in the Y-maze and novel object recognition tasks (SI Figure 11d, e); these deficits were significantly reversed by pretreatment with TC-2153 (SI Figure 11a-e).…”
Section: Resultsmentioning
confidence: 99%
“…Post-mortem studies in schizophrenia report alterations in NAAG (Reynolds and Reynolds, 2011; Ghose et al, 2009), indicating that NAAG may play a pivotal role in the pathophysiology of schizophrenia. Additional evidence stems from studies utilizing the PCP drug model of schizophrenia revealing that NAAG peptidase inhibitors prevent the behavioral and physiological effects of NMDA receptor antagonism in rodents (Olszewski et al, 2008; Olszewski et al, 2012; Zuo et al, 2012). …”
Section: 0 1h-mrs In Schizophreniamentioning
confidence: 99%
“…Inhibitors of glutamate carboxypeptidase II (GCPII), the enzyme that inactivates NAAG, elevate extracellular levels of the peptide and increase activation of this receptor (Adedoyin et al, 2010; Slusher et al, 1999; Zhong et al, 2006; Zuo et al, 2012). NAAG peptidase inhibitors are effective in animal models of several clinical conditions (Neale et al, 2005; 2011; Thomas et al, 2006; Wozniak et al, 2012) and rescue short-term memory impairment induced by a low dose of dizocilpine (MK801) (Olszewski et al, 2012b). This latter result suggested that these inhibitors also might affect learning or memory in mice in which cognition had not been artificially diminished.…”
Section: Introductionmentioning
confidence: 99%